Analisa Perawatan Mesin Inflassion dengan Metode Reliability Centered Maintenance - Rosihan, Rifda Ilahy; Sastra, Fikri Adi; Montororing, Yuri Delano Regent; Widyantoro, Murwan (universitas teuku umar, 2022)
Failure can affected production activities and increase product defects. In addition, damage to the machine can result in high maintenance costs and decreased reliability and availability of the machine. PT. Fujisei Metal Indonesia is a manufacturing company that produces evaporator products. In the process, the inflation machine on the rollbound line is often damaged. The purpose of this study was to determine the critical components of the inflation engine and to reduce maintenance costs on the inflation engine. The method used in this study is the Reliability Centered Maintenance Method so that it can reduce maintenance costs by 26%.